Human Rights in Territories Development Ways of Improvement (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article describes human potential, the systemic nature of human potential, the capitalization of the human factor, and the theoretical foundations of innovative development of personnel potential. Human potential is considered as a comprehensive indicator of the level of economic efficiency improvement in industrial enterprises. Also, proposals and recommendations on the development of human potential in industrial enterprises were developed based on the studied foreign experiences.